2015
DOI: 10.1038/srep15952
|View full text |Cite
|
Sign up to set email alerts
|

Initial amplification of the HPV18 genome proceeds via two distinct replication mechanisms

Abstract: Determining the mechanism of HPV18 replication is paramount for identifying possible drug targets against HPV infection. We used two-dimensional and three-dimensional gel electrophoresis techniques to identify replication intermediates arising during the initial amplification of HPV18 episomal genomes. We determined that the first rounds of HPV18 replication proceed via bidirectional theta structures; however, a notable accumulation of almost fully replicated HPV18 genomes indicates difficulties with the compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 62 publications
2
56
0
Order By: Relevance
“…It has become clear in recent years that HPVs activate the DNA damage response network during their replication to “invite” cellular replication and DNA repair proteins to their replication foci[ 50 ]. Moreover, it has been shown that HPV uses homologous recombination to efficiently replicate its genome[ 39 , 40 ]. The exact mechanism and all the necessary cellular partners are not yet known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has become clear in recent years that HPVs activate the DNA damage response network during their replication to “invite” cellular replication and DNA repair proteins to their replication foci[ 50 ]. Moreover, it has been shown that HPV uses homologous recombination to efficiently replicate its genome[ 39 , 40 ]. The exact mechanism and all the necessary cellular partners are not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…U2OS cells, which are derived from moderately differentiated osteosarcoma, have an adherent epithelial morphology and carry wild-type p53 and pRB genes, which have proven to be useful for studying various aspects of the HPV life cycle[ 36 38 ]. It has been shown that the replication mechanism of HPVs in U2OS cells is identical to other cell lines, such as HaCat cells[ 39 , 40 ]. In addition to describing replication, transcriptome analyses of mucosal HPVs 11 and 18 and cutaneous HPV 5 have been published[ 41 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…The viral E1 and E2 proteins are not present in the virion, so viral transcription with accompanying synthesis of these proteins is assumed to occur very early after infection. A recent study found that replication begins at the viral ori and proceeds through a theta structure model, although subsequent replication appeared to be unidirectional and did not initiate at a specific site [ 59 ]. Viral copy number is maintained in proliferating basal keratinocytes and in vitro cultured cells that carry PV episomes, which presumably requires viral origin licensing during G1/S after which the replicated genomes partition without triggering the mitotic spindle dependent checkpoint [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the productive life cycle in stratified epithelia, HPV genomes undergo three distinct modes of replication [ 28 , 29 ]. During the first phase, shortly after initial entry into the nucleus, there is a rapid increase in viral genome DNA replication to increase the stable episome copy number.…”
Section: Modes Of Hpv Genome Replicationmentioning
confidence: 99%
“…The third phase of vegetative amplification is characterized by the rapid production of high numbers of viral genomes, where evidence has been seen for both bidirectional theta replication and recombination-dependent replication (RDR; [ 29 ]). RDR is a viral replication mechanism that lacks specific ORI sequences and that can initiate replication within various regions of the HPV genome.…”
Section: Modes Of Hpv Genome Replicationmentioning
confidence: 99%